Lifestyle and the risk of acute coronary event: a retrospective study of patients after myocardial infarction - Szczepańska, Elżbieta; Białek-Dratwa, Agnieszka; Filipów, Katarzyna; Kowalski, Oskar (Frontiers in Nutrition, 2023)
Introduction: Unhealthy lifestyle behaviours that may contribute to the development of disorders leading to MI include consuming foods with a high glycaemic load and excessive supply of saturated fats, especially trans fats. Material and methods: The study included 116 patients of the Silesian Centre for Heart Diseases in Zabrze (SCCS) (Poland), with their average age being 59.45 ± 11.54 years, staying in the SCCS due to MI, from March to November 2022. The comprehensive assessment of diet quality included 72 patients: 15 women and 57 men. The research tool was the KomPAN questionnaire for examining dietary views and habits, developed by the Committee on Human Nutrition Science of the Polish Academy of Sciences, evaluating the diet in the year preceding the study. The following three indicators were used to assess the diet quality: pro-Healthy Diet Index (pHDI) , non-Healthy Diet Index (nHDI) and Diet Quality Index (DQI). Results: Most patients ate white wheat bread several times a day (39.66% of patients, with a higher percentage in men than in women—42.35% vs 32.26%), and white rice, fine-ground groats and pasta once a week (40.52% of patients, including 41.17% of men and 38.71% of women). Legume seeds were predominantly eaten 1–3 times a month (51.73% of responses, with comparable percentages of men and women, i.e. 51.76% vs 51.62%), vegetables several times a week (42.25% of responses, including more women than men, i.e. 54.84% vs 37.64%), and fruit once a day (40.52% of responses, including more men than women: 45.89% vs 25.81%). Conclusion: The results of our assessment of individual behaviours of the whole group may indicate errors in the diet. The value of the pro-Healthy Diet Index appears to confirm this fact, while the non-Healthy Diet Index and Diet Quality Index values do not clearly demonstrate its potential adverse impact on health. These limitations of our study may be due to differences in the size of the study population and the size of the population included in the comprehensive diet assessment. Therefore, it seems necessary to conduct further research.